Code Mixing Analysis Used by Facebookers: Code Mixing Analysis Used by Facebookers - Rotua Hutasoit; Novita Hutabarat (Institute of Computer Science (IOCS), 2020)
This thesis dealt with an analysis of code mixing using by facebooker. The objectives of the study are to describe types of code mixing by facebooker status, and to derive the dominant of code mixing in facebooker status. This study is limited only on analyzing the written status of facebooker in the same group. The data of the study was the status of facebooker. There were 40 status taken as the samples. This research was conducted by qualitative and quantitative method. The writer uses one technique of collecting data, mat is collecting the samples of facebooker status that using code mixing in facebook. The technique of analyzing data, the writer uses some steps, they are: identifying code mixing status of facebooker, classifying the sample of code mixing status based on Musysken's concept, converting the data number into percentages by using formula: X F/N x 100%. The writer found that there are three types of code mixing which are used in facebooker status. The dominant type is insertion (70.42%), then followed by alternation (16.90%), and the last is congruent lexicalization (12.68%). From the data analysis, the most dominant type is insertion.